IMPROVING SCHOOL ACCREDITATION THROUGH PRINCIPAL LEADERSHIP: A CASE STUDY IN MADRASAH TSANAWIYYAH - Al Qadri, Muhammad; Iskandar; Saiful Bahri; Sibawayhie, M Haris Miftah (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
Accreditation is a significant marker of school performance, influencing its competitiveness both nationally and internationally. This paper examines the role of the principal in improving accreditation at MTsS Ulumuddin, using a qualitative research approach. Data were gathered through interviews, observations, and documentation. The primary aim of this study is to explore how the leadership of the principal contributes to enhancing the school’s accreditation status. The findings emphasize the principal’s efforts in implementing the Merdeka Curriculum, fostering collaboration among teachers, students, and parents, and cultivating a culture of teacher reflection. These strategies directly contribute to improving the school’s accreditation. Additionally, the principal ensures the integration of technology in the learning process, customizes the curriculum to meet the diverse needs of students, and manages the school budget efficiently and transparently. By focusing on these areas, the principal drives the achievement of higher educational standards, which is essential for improving school accreditation. The study underscores the importance of strong leadership in advancing educational quality and accreditation, highlighting the principal’s proactive approach in aligning school operations with national standards and goals. Overall, this paper demonstrates that effective school leadership is a critical factor in improving both the accreditation process and educational outcomes. Keywords: Leadership; Principal; Accreditation; Merdeka Curriculum; Educational Standards. Abstrak Akreditasi merupakan penanda penting kinerja sekolah, yang memengaruhi daya saing baik secara nasional maupun internasional. Artikel ini mengkaji peran kepala sekolah dalam meningkatkan akreditasi di MTsS Ulumuddin. Menggunakan pendekatan penelitian kualitatif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Tujuan utama penelitian ini adalah untuk mengeksplorasi kepemimpinan kepala sekolah berkontribusi dalam meningkatkan status akreditasi sekolah. Temuan penelitian ini menekankan upaya kepala sekolah dalam menerapkan kurikulum merdeka, mendorong kolaborasi antara guru, siswa, dan orang tua, serta menumbuhkan budaya refleksi guru. Strategi ini secara langsung berkontribusi dalam meningkatkan akreditasi sekolah. Selain itu, kepala sekolah memastikan integrasi teknologi dalam proses pembelajaran, menyesuaikan kurikulum untuk memenuhi beragam kebutuhan siswa, dan mengelola anggaran sekolah secara efisien dan transparan. Dengan berfokus pada area ini, kepala sekolah mendorong pencapaian standar pendidikan yang lebih tinggi, yang penting untuk meningkatkan akreditasi sekolah. Studi ini menggarisbawahi pentingnya kepemimpinan yang kuat dalam memajukan kualitas dan akreditasi pendidikan, dengan menyoroti pendekatan proaktif kepala sekolah dalam menyelaraskan operasional sekolah dengan standar dan tujuan nasional. Secara keseluruhan, artikel ini menunjukkan bahwa kepemimpinan sekolah yang efektif merupakan faktor penting dalam meningkatkan proses akreditasi dan hasil pendidikan. Kata kunci: Kepemimpinan; Kepala Sekolah; Akreditasi; Kurikulum Merdeka; Standar Pendidikan.